Analysis Of The Influence Of e-WOM On Shopee Online Purchase Decisions: Systematic Literature Review (SLR) With Bibliometrics - Gunawan Santoso; Budi Eko Soetjipto; Madziatul Churiyah (PT. Maju Malaqbi Makkarana, 2026)
This study aims to analyze the influence of electronic word of mouth (eWOM) on online purchase decisions on the Shopee platform through the Systematic Literature Review (SLR) approach combined with bibliometric analysis. This study systematically examined various relevant scientific articles from reputable databases over a period of time to identify research trends, collaboration patterns, and developments of eWOM concepts in the context of e-commerce. The literature selection process was carried out using strict inclusion and exclusion criteria to ensure the quality and relevance of the studies analyzed. Furthermore, bibliometric analysis is used to map influential keywords, authors, and citation networks in this topic. The results showed that eWOM had a positive and significant influence on online purchasing decisions, which were mediated by trust factors, risk perception, information quality, and source credibility. In addition, it was found that the trend of eWOM research on the Shopee platform has increased significantly in line with the development of digital commerce and online review-based consumer behavior. This research contributes to enriching the literature review related to eWOM and provides practical implications for business people in optimizing digital marketing strategies based on consumer reviews.